Determinants of Underemployment and Its Implications for Household Poverty: Evidence from a Poverty-Prone Region in Indonesia - Nopiah, Ririn; Romi Gunawan; Izharudin, Izharudin; Jesica Dinda Claudia Manalu (International Journal of Economics, Business and Innovation Research, 2025)
Underemployment and poverty represent significant challenges for regional economies. This study aims to examine the determinants of underemployment and its impact on household poverty in Bengkulu Province. The research employs multinomial logistic regression and logistic regression methods. The findings indicate that poverty status, age, and employment position, such as self-employment and unpaid family work, positively influence the likelihood of underemployment. Conversely, economic status, area of residence (urban or rural), productive age, gender, marital status, and household size negatively affect the risk of underemployment. On the other hand, poverty is significantly influenced by employment status, area of residence (particularly in rural areas), non-productive age, marital status, household size, and education level. Individuals or households with lower levels of education face a higher probability of experiencing poverty. The study further reveals that individuals working fewer than or equal to 34 hours per week are 1.6% more likely to fall into poverty. These results underscore the need for policies that expand access to basic services, improve access to formal employment, enhance the quality of life for informal workers, and provide special attention to micro, small, and medium enterprises (MSMEs) as strategies to reduce both underemployment and poverty.